Extracellular vesicles facilitate large‐scale dynamic exchange of proteins and RNA among cultured Chinese hamster ovary and human cells. Issue 5 (14th February 2022) - Belliveau, Jessica; Papoutsakis, Eleftherios T.
Abstract: Cells in culture are viewed as unique individuals in a large population communicating through extracellular molecules and, more recently extracellular vesicles (EVs). Our data here paint a different picture: large‐scale exchange of cellular material through EVs. To visualize the dynamic production and cellular uptake of EVs, we used correlative confocal microscopy and scanning electron microscopy, as well as flow cytometry to interrogate labeled cells. Using cells expressing fluorescent proteins (GFP, miRFP703) and cells tagged with protein and RNA dyes, we show that Chinese hamster ovary (CHO) cells dynamically produce and uptake EVs to exchange proteins and RNAs at a large scale. Applying a simple model to our data, we estimate, for the first time, the per cell‐specific rates of EV production (68 and 203 microparticles and exosomes, respectively, per day). This EV‐mediated massive exchange of cellular material observed in CHO cultures was also observed in cultured human CHRF‐288‐11 and primary hematopoietic stem and progenitor cells. This study demonstrates an underappreciated massive protein and RNA exchange between cells mediated by EVs spanning cell type, suggesting that the proximity of cells in normal and tumor tissues may also result in prolific exchange of cellular material. This exchange would be expected to homogenize the cell‐population cytosol and dynamically regulate cell proliferation and the cellular state. Abstract : Characterizing extracellular vesicle (EV) exchange is critical yet underexplored for evaluating the dynamic exchange of protein and RNA material among cultured mammalian cells. This investigation of fluorescent Chinese hamster ovary (CHO) cell cocultures demonstrates EV exchange through both correlative light and electron microscopy and flow cytometry. By applying a simple model to the accumulation of EVs in the media, the specific rates of EV production per cell were estimated for two types of CHO EVs, microparticles and exosomes.